Penyakit Kusta dan Peran Serta Masyarakat di Wilayah Kerja Puskesmas Batumarta II Kabupaten OKU Tahun 2021 - Amrina Yulita; Erma Gustina; Yusnilasari Yusnilasari (Jurnal Kesehatan Saelmakers PERDANA, 2022)
The Word Health (WHO) recorded the number of new cases of leprosy in the word in 2016 was around 210.758. Of this number, the most area in the Southeast Asia region (156118). Data profile of the Health Office Ogan Komering Ulu shows that the number of leprosy cases in Kab.OKU in the last 5 years, namely <1/10.000 population, and the number of disable cases >5% means that it exceeds the national target.Kab OKU. The research aimed to analysis the inhibition of the leprosy patients medication: patients roles (knowledge, attitude and trust); families role, community role, health in the working area of UPTD Puskesmas Batumarta II Kab.OKU regency in 2021. This was a qualitative research with the phenomenological approach. Informants in the research were as many as twenty one informants consisting of the leprosy petients of types PB and PB, patients families, community figures, and health afficials. Data were obtained from an interview and observasion. The data analysistematik. The research result indicates that the different informants knowledge concerning the leprosy disease. The patients are not active in responding the reactions occurring in the bodies. The patients tend to be sensitive if their diseases are know by other people.The inhibition from the families is caused by not comprehending well concerning PHBS and it is regarded as a shameful and hereditary disease. The inhibition from the community role because the is the community stigma of society that views leprosy as a curse or skin disease. The inhibition of the health offcials role is because they are often busy with other work, so that the patients medication is sometimes negiected and there is a household contact with the leprosy patients who postpone the medication, the patients refuse to be examined in their homes, so that their disease can be spread to otherpeople.